A closed‐form expression for the coverage of cellular systems under Hoyt (Nakagami-q) fading. - Martín-Vega, Francisco-Javier; Gómez-Paredes, Gerardo; López-Martínez, Francisco Javier; Aguayo-Torres, María del Carmen (Wiley, 2017)
A simple closed-form expression is provided for the coverage probability of cellular systems under Hoyt (Nakagami-q) fading, which models fading scenarios more severe than Rayleigh. The accuracy of the proposed framework is validated through Monte Carlo simulations
Política de acceso abierto tomada de:https://digital-library.theiet.org/files/Author_self-archiving_policy.pdf
Keywords: Teléfonos móviles; Comunicaciones; Stochastic geometry; Communication theory; Hoyt fading; Cellular networks